Investigating the interaction between neuropsychiatry features and daily activities on social function in patients with Parkinson's disease with mild cognitive impairment. Issue 6 (25th November 2022) - Chen, Yi-Ru; Tan, Chun-Hsiang; Su, Hui-Chen; Chien, Chung-Yao; Sung, Pi-Shan; Lin, Tien-Yu; Lee, Tsung-Lin; Yu, Rwei-Ling
Abstract : Background: Social functioning is crucial for daily living and is an essential indicator of dementia in patients with Parkinson's disease. The pattern of social functioning in patients with Parkinson's disease without dementia (i.e. those who are cognitively intact or have mild cognitive impairment (PD-MCI)) and its determinants are unclear. Aims: In exploring the heterogeneity of social functioning among patients with Parkinson's disease-associated dementia, we determined the optimal cut-off score of the Parkinson's Disease Social Functioning Scale (PDSFS) for patients with PD-MCI, and the variables influencing patients' social functioning. Method: A total of 302 participants underwent the Mini-Mental State Examination (MMSE) and PDSFS; 120 patients with Parkinson's disease completed the measurements (MMSE, Activities of Daily Living Scale and Neuropsychiatric Inventory). Group comparisons, receiver operating characteristic curves, Spearman correlation and multiple and hierarchical regression analyses were conducted. Results: The PD-MCI group scored the lowest on the PDSFS ( F = 10.10, P < 0.001). The PDSFS cut-off score was 53 (area under the curve 0.700, sensitivity 0.800, specificity 0.534). The MMSE ( β = 0.293, P = 0.002), Activities of Daily Living Scale ( β = 0.189, P = 0.028) and Neuropsychiatric Inventory ( β = −0.216, P = 0.005) scores predicted the PDSFS score. Further, there was an interaction effect between the Activities of Daily Living Scale and Neuropsychiatric Inventory scores on the PDSFS score ( β = 0.305, P < 0.001). Conclusions: We determined a PDSFS cut-off score for detecting PD-MCI and found that patients with PD-MCI have social dysfunction. Future research should focus on the effects of neuropsychiatry symptoms and activities of daily living on social functioning, and tailor the intervention programme for patients with Parkinson's disease.